EKSPLORASI ETNOMATEMATIKA DALAM PERMAINAN TRADISIONAL LOMPAT TALI PADA PEMBELAJARAN BERHITUNG SISWA KELAS II SEKOLAH DASAR - Widya Sahasika; Feny Rita Fiantika; Prayogo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore and introduce ethnomathematics-based learning through the traditional rope-skipping game at SDN Margorejo Surabaya, especially in class II-A. The method used in this study is qualitative, which relies on in-depth descriptions of data and facts surrounding the subject being studied. In this context, an ethnographic approach was chosen to understand the concept of numbers in mathematics contained in the traditional rope-skipping game. The research data were collected from class II-A at SDN Margorejo I Surabaya. Data collection techniques include student assignment sheets, written tests, and interviews. Furthermore, data analysis was carried out through the process of data reduction, data presentation, and drawing conclusions. The results of the study, which applied the triangulation technique, showed that there was a similarity in meaning between the results of the written test and the results of the interview, which indicated the validity and credibility of the study. This shows that the application of the traditional rope-skipping game can link mathematical concepts, especially number material.